Spontaneous haemorrhage into metastatic brain tumours after stereotactic radiosurgery using a linear accelerator. Issue 7 (1st July 2003) - Suzuki, H; Toyoda, S; Muramatsu, M; Shimizu, T; Kojima, T; Taki, W
Abstract : Objective: To determine the incidence and clinical characteristics of spontaneous haemorrhage into metastatic brain tumours after radiosurgery. Methods: Intratumour haemorrhage rate, clinical features, and treatment were evaluated in 54 patients with 131 brain metastases of varying origin who were treated using linear accelerator radiosurgery. The marginal dose was maintained constant at 20 or 25 Gy, irrespective of tumour size. Results: Haemorrhage was identified in 7.4% of the metastases (five tumours in four patients) before radiosurgery and in 18.5% (10 tumours in 10 patients) after radiosurgery. In three cases, haemorrhage into the tumour after radiosurgery was symptomatic. Half the haemorrhages occurred within one month of radiosurgery. The changes in tumour size observed at the time of haemorrhage were an increase in one tumour, no change in five, and a decrease in four. Haemorrhage into a tumour after radiosurgery was more likely to occur in female patients, in tumours with a larger volume on pretreatment neuroimaging, and in tumours treated with a larger number of isocentres or a higher maximum dose. Haemorrhagic features in the patients or their tumours on presurgical assessment were not disposing factors to haemorrhage after radiosurgery. Conclusions: When larger brain metastases are aggressively treated by radiosurgery, better local control may be attained but there may also be a higher risk of haemorrhage soon after the treatment.